PENGARUH APLIKASI MARBEL BELAJAR BERHITUNG TERHADAP KECERDASAN MATHEMATICS ANAK USIA 5–6 TAHUN DI TK PEMBINA 1 KOTA JAMBI - Putri Krise Lestari; Hendra Sofyan; Muhammad Sofwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of using the "Marbel Belajar Berhitung" application on the mathematical intelligence of children aged 5-6 years. The primary issue addressed is the low basic numeracy skills of children, often resulting from the dominance of conventional and non-interactive learning methods. This research employed a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The sample consisted of 30 children at TK Pembina 1 Kota Jambi, divided into experimental and control groups through purposive sampling. Data were collected using validated mathematical ability observation sheets, encompassing both pre-test and post-test measurements. Statistical analysis using the Mann-Whitney U test yielded a significance value of 0.000 (p < 0.05). The experimental group using the Marbel application achieved a mean post-test score of 82.45, significantly outperforming the control group which scored 58.60. These findings demonstrate that the Marbel Belajar Berhitung application significantly enhances children's mathematical intelligence through visual stimulation and interactive gaming elements. The study concludes that the integration of educational digital media is highly effective in optimizing cognitive development at the early childhood education level. Practical implications emphasize the importance of transforming digital learning media as an innovative solution to improve the quality of numeracy education in schools.